Imaging Postoperative Abdominal Hernias: A Review with a Clinical Perspective - Chatterjee, Argha; Ramanan, Rochita V.; Mukhopadhyay, Sumit (Journal of Gastrointestinal and Abdominal Radiology, 2020)
Postoperative internal hernia is a challenging but critical diagnosis in postoperative patients presenting with acute abdomen. Postoperative internal hernias are increasingly being recognized after Roux-en-Y gastric bypass (RYGB) and bariatric surgeries. These internal hernias have a high risk of closed-loop obstruction and bowel ischemia; therefore, prompt recognition is necessary. Computed tomography (CT) is the imaging modality of choice in cases of postoperative acute abdomen. Understanding the types of postoperative internal hernia and their common imaging features on CT is crucial for the abdominal radiologist. Postoperative external hernias are usually a result of defect or weakness of the abdominal wall created because of the surgery. CT helps in the detection, delineation, diagnosis of complications, and surgical planning of an external hernia. In this article, the anatomy, pathophysiology, and CT features of common postoperative hernias are discussed. Afterreading this review, the readers should be able to (1) enumerate the common postoperative internal and external abdominal hernias, (2) explain the pathophysiology and surgical anatomy of Roux-en-Y gastric bypass-related hernia, (3) identify the common imaging features of postoperative hernia, and (4) diagnose the complications of postoperative hernias.
Keywords: internal hernia; incisional hernia; computed tomography